About the relationship between territory, memory and resistance. a reflection concept derived from experience peasant sumapaz (2014)
This article aims to deploy a profound significance of the concepts of territory, memory and resistance in its relational dimension, from the research experience conducted in the Sumapaz region. It begins by developing the idea of territory with the contrast of Euclidean space and formal and the conception that criticism Geography has made explicit in the last thirty years from the subjective, the community and the political. This will display the recurrence of the sumapaceña peasant organization in this second meaning of space as socially constructed territory. In a third stage, the exercise of collective memory is displayed as a necessary step for consolidation of peasant resistance and the historical reproduction of territoriality.